An oral formulation of efavirenz‐loaded lactoferrin nanoparticles with improved biodistribution and pharmacokinetic profile. Issue 7 (21st December 2016) - Kumar, P; Lakshmi, YS; Kondapi, AK
Abstract : Objectives: Efavirenz (EFV), a non‐nucleoside reverse transcriptase inhibitor, is a drug that is frequently included in highly active antiretroviral therapy for treatment of HIV infection. Decreased bioavailability and increased toxicity limit its use. We report a formulation of efavirenz‐loaded lactoferrin nanoparticles (lacto‐EFV‐nano) for oral delivery which exhibited significantly improved pharmacological properties coupled with reduced toxicity compared with its free form. Methods: Lacto‐EFV‐nano was prepared using the Sol‐oil protocol and characterized using various sources of characterization. In vitro and in vivo studies were performed to test the stability, safety, efficacy, biodistribution and pharmacokinetics of lacto‐EFV‐nano. Results: The nanoparticles prepared for the present study had an average size of 45−60 nm as revealed by field emission scanning electron microscope measurements. Further, dynamic light scattering data showed a hydrodynamic radius of 103 ± 5.3 nm, a zeta potential of −23 ± 1.2 mV and a polydispersity index of < 0.341. Lacto‐EFV‐nano was found to be stable as assessed using differential scanning calorimetry and Fourier‐transform infrared spectroscopy. Cell viability studies showed that lacto‐EFV‐nano was at least 2‐fold less toxic to peripheral blood mononuclear cells, Jurkat T cell and B16‐F10 cell lines than free EFV. Furthermore, lacto‐EFV‐nano [50% inhibitory concentration (IC50 ) < 1.1 nM] showed > 2‐fold enhanced anti‐HIV‐1 activity compared with free EFV (IC50 = 2.56 nM). Lacto‐EFV‐nano exhibited improved oral bioavailability and an improved in vivo pharmacokinetic profile, with a > 3−4‐fold increase in the area under the plasma concentration−time curve (AUC), a 6−7‐fold increase in the area under the first moment curve (AUMC), a > 30% increase in the peak plasma concentration of the drug after oral administration ( C max ) and a 2‐fold increase in the time to reach C max ( T max ) and the time required for the concentration of the drug to reach half of its original value ( t 1/2 ). Furthermore, lacto‐EFV‐nano did not show any organ‐related toxicity. A significant decrease in the concentrations of various parameters, elevated concentrations of which are markers of reduced safety, were also observed in rats treated with lacto‐EFV‐nano. Conclusions: Compared with free EFV, lacto‐EFV‐nano is a promising oral nanoformulation with enhanced bioavailability and efficacy of EFV and improved safety.